The German pediatric integrated care survey (PICS-D): Translation, adaptation, and psychometric testing - Willems, Jana; Bablok, Isabella; Sehlbrede, Matthias; Farin-Glattacker, Erik; Langer, Thorsten (Frontiers in Pediatrics, 2022)
Background: Integrated care models aim to strengthen the collaboration between healthcare sectors to ensure a higher quality of care for children with chronic conditions. Assessing pediatric healthcare integration through families’ experiences, therefore, is essential. Our study aimed to psychometrically test the PICS-D, the first German-language integrated care questionnaire, which is based on the Pediatric Integrated Care Survey (PICS) developed in the USA. Methods: We examined construct validity using exploratory and confirmatory factor analyses (structural validity). Cronbach’s α and McDonald's ωt coefficients explored reliability. Cognitive interviews assessed wording comprehension and item appropriateness. Results: PICS-D was completed by 204 caregivers of children with chronic conditions (women = 84%; mean age = 41.4 years). Factor analyses identified 3 factors: “Team quality & communication”, “Family impact”, and “Access to care”. The 3-factorial structure showed a satisfying fit to confirmatory classical-test-theory-based models. Due to the insufficient reliability of the third factor, we recommend using only factors 1 and 2 for scoring the PICS-D. Conclusion: The PICS-D is a 13-item questionnaire to assess family-reported experiences in pediatric care integration, which has good psychometric properties. It may be useful in guiding quality improvement efforts or measuring the impact of a care plan or care model. Trial registration: German Clinical Trials Register (DRKS): DRKS00018778; Trial registration date 05. December 2019 - Retrospectively registered; https://apps.who.int/trialsearch/Trial2.aspx?TrialID=DRKS00018778.